Wind Turbine Emulator Using Induction Motor Driven by Frequency Inverter and Hardware-in-the-loop Control - Oliveira, Jose Rodrigo de [UNESP]; Souza, Wallace Gabriel de [UNESP]; Rocha, Marco Aurelio [UNESP]; Costa, Christielly Fernandes da [UNESP]; Ferraz Leao, Jose Vital [UNESP]; Andreoli, Andre Luiz [UNESP]; Tsuzuki, MDG; Junqueira, F. (Ieee, 2018)
This work presents the development of a wind turbine emulator which consists of an induction motor driven by a frequency inverter. The aim of this paper is to propose a hardware setup, which allows testing wind energy systems for evaluation of power quality, reliability and performance in a laboratory environment. The wind turbine emulator algorithm was modeled and simulated using MATLAB/Simulink (R) software. Besides, the communication between this software and the workbench is guaranteed by a DSP TMS320F28335. Experimental results confirm that the wind turbine emulator performance was satisfactory, since it was capable to represent a real one.
Keywords: Wind turbine emulator; induction motor; frequency inverter; wind energy systems